Effects of a Freshening Boundary Currenton on Deep Convection and Eddy Activity in the Labrador Sea - van Dam, Tim (author) (2018)
A freshening of the boundary current (Labrador current and West Greenland Current) supresses deep convection in the Labrador Sea. Furthermore, the fresher water contributes to the ``strength'' of Irminger Rings and increases their life time. This leads to a larger spread of high EKE into the interior of the Labrador Sea and confines the deep convection region more towards the west. VIDI Additional thesis